Peningkatan Pengetahuan Warga Bromonilan untuk Mencegah Kejadian dan Komplikasi Diabetes Melitus Tipe II - Fidianingsih, Ika; Sulistyoningrum, Evy; Kharisma, Muhammad (Universitas Ahmad Dahlan, 2017)
Background: Almost 80% of Diabetes Mellitus (DM) in the world is found in developing countries, and incidence of diabetes mellitus continues to increase, including in Indonesia. This disease will lead to decreased productivity and increased the economic burden in patient DM.Â Bromonilan who suffer from DM is found the death of DM while the mortality rate of Bromonilan was unreported. The purpose of the study was to know the prevalence of Bromonilanâs DM. Method: A study was carried out in 80 of Bromonilan Villagers. All of the samples were measured the level of knowledge of DM through pretest and posted. Measuring glucose levels were also performed on 80 Bromonilan using rapid tests. Result: The prevalence of Bromonilan affected by DM was 10%. The level knowledge of DM increased 39.3% by intervention test. Conclusion: The prevalence of DM in Bromonilan was quite high. Integrated health services in community serve simultaneously to improve their knowledge such DM.